The Physical Environmental Stressors Mitigating Effective Caregiving in Nigerian General Hospitals : A Case Study of Kaduna State - Abubakar Alkali, Ibrahim; Aisara, Abdullahi; Gidado Mai, Muhammad (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Stress has been identified to be one of the major challenges of healthcare settings that causes turnover and burnout of caregivers and also a negative consequences on patient recovery. It is a common condition that has a significant negative consequences on the well-being of users of healthcare environment. It has been established that, Healthcare environment have tendencies of aggravating or reducing stress, but very little information is available on its role in relation to stress in Nigeria. In this regard, this research is aimed at examining the mitigating effects of environmental stressors on effective caregiving in General hospitals. A case study of four (4) General Hospitals in Kaduna State (Hajiya Gambo Sawaba, Giwa, Kauru and Sarkin Maska Shehu in Funtua) was carried out to explore the stressors of healthcare environment and their resultant effects. In addition to observation, Twenty-four healthcare personnel comprising of nurses and doctors were selected using purposively sampling and interviewed. The data was analysed using content analysis. Two environmental stressors found in healthcare environment are ambient and facility layout in nature. It was also found that there was less conscious attempt to use stress reducing-measures in minimising stress on the users. Therefore, it becomes pertinent to use design strategies and elements inherent with stress-relieving effects to minimise stress in future designs of general hospitals in the country.